2016
DOI: 10.1101/049882
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Activated Ras/JNK driven Dilp8 in imaginal discs adversely affects organismal homeostasis during early pupal stage inDrosophila, a new checkpoint for development

Abstract: One sentence AbstractElevated JNK activity following predominant over-expression of activated Ras or Reaper or Tak1 in Drosophila larval eye discs does not delay pupation but reduces post-pupariation ecdysone pulse via elevated Dilp8 and reduced Ptth, which results in early pupal death. AbstractWe examined reasons for early pupal death following expression of certain transgenes with predominantly eye-disc specific GMR-GAL4 or sev-GAL4 drivers in Drosophila. The GMR-GAL4 or sev-GAL4 driven expression of UAS-Ras… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Evolution of multi-cellularity and the associated division of labour between different cell types has necessitated inter-cellular signaling pathways with complex network of regulatory circuits. The evolution of biological complexity has also been paralleled by substantial increase in the non-coding component in diverse genomes, and there is increasing realization in recent years that the large varieties of short and long non-coding RNAs (lncRNA) have great roles in cell signaling and gene regulation (Geisler and Coller, 2013;Huang et al, 2013;Jose, 2015;Lakhotia, 2016;Lakhotia, 2017a;Lakhotia, 2017b;Mattick and Makunin, 2006;Morris and Mattick, 2014;Peng et al, 2017). The lncRNAs like acal, mrhl, CRNDE, LncND, and URHC have been reported to regulate JNK, Wnt, insulin, Notch and ERK/MAPK signaling pathways, respectively (Arun et al, 2012;Ellis et al, 2014;Katsushima et al, 2016;Ríos-Barrera et al, 2015;Xu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evolution of multi-cellularity and the associated division of labour between different cell types has necessitated inter-cellular signaling pathways with complex network of regulatory circuits. The evolution of biological complexity has also been paralleled by substantial increase in the non-coding component in diverse genomes, and there is increasing realization in recent years that the large varieties of short and long non-coding RNAs (lncRNA) have great roles in cell signaling and gene regulation (Geisler and Coller, 2013;Huang et al, 2013;Jose, 2015;Lakhotia, 2016;Lakhotia, 2017a;Lakhotia, 2017b;Mattick and Makunin, 2006;Morris and Mattick, 2014;Peng et al, 2017). The lncRNAs like acal, mrhl, CRNDE, LncND, and URHC have been reported to regulate JNK, Wnt, insulin, Notch and ERK/MAPK signaling pathways, respectively (Arun et al, 2012;Ellis et al, 2014;Katsushima et al, 2016;Ríos-Barrera et al, 2015;Xu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The lncRNAs like acal, mrhl, CRNDE, LncND, and URHC have been reported to regulate JNK, Wnt, insulin, Notch and ERK/MAPK signaling pathways, respectively (Arun et al, 2012;Ellis et al, 2014;Katsushima et al, 2016;Ríos-Barrera et al, 2015;Xu et al, 2014). Besides their roles in developmental regulation (Katsushima et al, 2016;Kotake et al, 2016;Lakhotia, 2017b;Misawa et al, 2017;Zhang et al, 2017a), diverse lncRNAs have been reported to interact with components of the various signaling pathways in cancer, activating or repressing their strength and thus affecting outcomes like cell proliferation or apoptosis (Lakhotia, 2016;Liu et al, 2015;Wang et al, 2015). An earlier study (Ray and Lakhotia, 1998) from our laboratory showed that mutant alleles of ras (ras E62K and ras D38N ) dominantly enhanced the lethality due to nullisomic condition of the hsrω gene, which produces multiple lncRNAs (Lakhotia, 2011;Lakhotia, 2017a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An early version of this study was published as a preprint. 12 This study shows that elevated Ras signaling can also contribute to Dilp8 expression and that activated Ras signaling in a particular tissue has far-reaching consequences on distant organs. It also highlights susceptibility of certain stages of development to specific changes in signaling events, particularly that of Dilp8 on pupal developmental processes and its importance as messenger between epithelia and brain.…”
Section: Introductionmentioning
confidence: 77%
“…These results thus unravel the early pupal ecdysone surge as a new checkpoint for Dilp8 action and explain the intriguing results noted in several other studies that expression of certain transgenes by predominantly eye disc specific GAL4 drivers is associated with pupal lethality. An early version of this study was published as a preprint …”
Section: Introductionmentioning
confidence: 99%